ZAHIR BEYBARS IS A GREAT COMMANDER (Spectrum Journal of Innovation, Reforms and Development, 2023)
This scientific article investigates and analyzes the processes of formation of the sovereignty of the Mamluks who dominated Egypt in 1250-1517, the events that led to the arrival of the Egyptians to Egypt, the reign of Sultan Zahir Beibars and his relationship with the Abbasid caliphs were studied and analyzed.